Quantitative assessment and optimization of bi-functional membrane for remediation of Cr(VI) from wastewater - Arif Z.; Sethy N.K. (My University, 2025)
This paper explores the innovative approach of using a green route synthesized cost-effective bi-functional to eliminate toxic hexavalent chromium commonly found in tannery wastewater by using an integrated application of membrane and photocatalyst. Contaminated wastewater is firstly passed through bi-functional ultrafiltration membranes to retain hexavalent chromium and further reducing the toxicity of rejected water having high concentrations of Cr(VI) by photocatalytic reduction into Cr(III) in the presence of sunlight using the same membrane as photocatalyst film. Conditions governing the separation process such as solution pH, nanoparticle loading in polymer matrix, and concentration of Cr(VI) have been optimized to maximize the % rejection and photocatalytic reduction to Cr(III). The purpose of this work was to optimize the process condition through the use of the response surface method (RSM) that governs the process. RSM analysis concludes that excellent rejection of 91.58% and reduction of 87.02% is possible at the predicted pH (5.55), particle loading (2.14%) and Cr(VI) concentration (25 mg/L). © 2022 The Authors.